Dilution Control and Vibration Studies at an Underground Mine - B Mohanty; R Yang; M Leblanc (International Society of Explosives Engineers, 1995)
A total of 33 blasts in the pillar recovery program at INCO-Crean Hill has been investigated by means of an extensive set of diagnostic techniques. These included, borehole deviation measurements, stope cavity survey, near-field seismics in both rock and backfill, in-hole VOD and fragment size analysis. The 200 mm diameter VCR blasts employed a variety of explosives types (ANFO, slurry and ANFO/Polystyrene) and deck sizes. The objective of the investigation was to control dilution and backbreak through optimal choice of explosive type and charge weight, without exceeding vibration limits in the adjacent backfill or causing significant degradation in fragmentation.